Fodder research embedded in a system of innovation - Bezkorowajnyj, P.G.; Prasad, V.L.; Dhamankar, M.; Roothaert, Ralph L.; Olufajo, O.O.; Romney, Dannie L. (International Livestock Research Institute, 2006)
A 3-year project implemented in India and Nigeria addressed the issue of improving livelihoods of poor livestock keepers by improving availability of fodder. The original approach focused on testing of new crop varieties to be scaled up through partners using mechanisms such as farmer-to-farmer exchange and field days. As the project evolved, it became clearer that the systems were much more complex than originally thought with a wide range of actors involved. Although fodder technology is obviously a requirement to reduce fodder shortages, many of the problems are embedded in the institutions and policies that determine how technology is developed and delivered. To help address these issues, an innovation systems approach is proposed with a focus on building capacity within the system.